Cardiopulmonary Effects of COVID-19 Vaccination: A Comprehensive Narrative Review - Lauren T. Forchette; Luis Palma; Christian Sanchez; Rebecca M. Gibons; Christoph A. Stephenson-Moe; Benjamin J. Behers (Vaccines)
Coronavirus disease 2019 (COVID-19) messenger RNA (mRNA) vaccines have been associated with numerous side effects since their widespread release to the public. Cardiovascular complications include myocarditis and pericarditis, Takotsubo cardiomyopathy, postural orthostatic tachycardia syndrome (POTS), arrhythmias, sudden cardiac death, and cardiac tamponade. Pulmonary complications are pulmonary embolism (PE), interstitial lung disease (ILD), idiopathic pulmonary fibrosis (IPF), pneumonia, eosinophilic granulomatosis with polyangiitis, pneumonitis, and pulmonary hypertension. Despite these complications, the risk–benefit analysis still strongly favors vaccination, as these events occur more frequently with natural infection and confer a significantly worse prognosis. This study outlines the evidence surrounding each attributed effect, the clinical course including diagnosis and management, and the proposed pathophysiology. To our knowledge, this is the most comprehensive review of the cardiopulmonary effects of COVID-19 vaccination to date.